2021
DOI: 10.3390/nu13124437
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil Extracts and Oleic Acid Attenuate the LPS-Induced Inflammatory Response in Murine RAW264.7 Macrophages but Induce the Release of Prostaglandin E2

Abstract: Olive oil contains high amounts of oleic acid (OA). Although OA has been described to inhibit inflammatory processes, the effects of olive oil on cellular mechanisms remain poorly understood. Therefore, we compared the effects of major fatty acids (FA) from olive oil with those of olive oil extracts (OOE) on inflammatory mediators and alterations in the cellular phospholipid composition in murine macrophages. Upon treatment with different OOE, FA compositions of lipopolysaccharide (LPS)-stimulated murine RAW26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…OLA can reduce the LPS-induced expression of iNOS, COX-2, and IL-6 mRNA and significantly decrease COX-2 and iNOS protein expression. 35 Therefore, OLA : menthol can preserve cell viability and reduce inflammation. These results corroborate with several previous studies that demonstrated the low toxicity of DESs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OLA can reduce the LPS-induced expression of iNOS, COX-2, and IL-6 mRNA and significantly decrease COX-2 and iNOS protein expression. 35 Therefore, OLA : menthol can preserve cell viability and reduce inflammation. These results corroborate with several previous studies that demonstrated the low toxicity of DESs.…”
Section: Resultsmentioning
confidence: 99%
“…Through the activation of NF-kB, OLA is linked to COX-2 and iNOS downregulation. 34,35 At the 1 : 2, 1 : 1, and 2 : 1 molar ratios of fatty acid-: menthol, a decreasing trend of cell toxicity with high menthol proportion was observed. Menthol has immunomodulatory and anti-inammatory effects in ethanol-induced gastric ulcers, where it reduces the pro-inammatory cytokines, TNF-a, and IL-6, while increasing the levels of the anti-inammatory cytokine IL-10.…”
Section: Anti-inammatory and Cytotoxicity Evaluation Of Hdessmentioning
confidence: 91%
“…The described effects of the MTD are based on a unique combination of high extra virgin olive oil (EVOO), oily-fish and vegetables consumption. EVOO has in vitro proven anti-inflammation effects of polyphenols on macrophages [ 36 , 37 ], including the reduction in NO release and iNOS expression. Fish oil in human studies represents the inhibition of inflammation-related genes expression in macrophages [ 38 ] and fresh vegetables, especially cruciferous, are pointed out by outstanding anti-inflammatory properties through biological-active compounds, which promote the M2 (anti-inflammatory) type of macrophage proliferation [ 39 ].…”
Section: The Role Of Diet Patterns and Food Groupsmentioning
confidence: 99%
“…Probiotics by definition are “ live microorganisms which when administered in adequate amounts confer a health benefit on the host ” [ 131 , 132 ]. They have been used to enhance male reproduction, owing to their ability to protect the intestinal barrier, inhibit pathogen growth and activate the immune response [ 133 , 134 ].…”
Section: Introductionmentioning
confidence: 99%